CD9 Gene Deficiency Does not Affect Smooth Muscle Cell Migration and Neointima Formation after Vascular Injury in Mice - Lijnen, H. R.; Lupu, F.; Collen, D.; Le Naour, F.; Boucheix, C. (Thrombosis and Haemostasis, 2000)
The hypothesis that CD9, a member of the tetraspanin family, plays a role in smooth muscle cell (SMC) migration was tested with the use of a vascular injury model in wild-type (CD9+/+) and CD9-deficient (CD9−/−) mice. Neointima formation 3 weeks after electric injury of the femoral artery was not significantly different in CD9+/+ and CD9−/− mice (area of 0.019 ± 0.0034 mm2 versus 0.013 ± 0.0036 mm2; mean ± SEM, n = 6). The medial areas were also comparable, resulting in intima/media ratio’s of 1.3 ± 0.15 and 0.90 ± 0.22, respectively. Nuclear cell counts in cross-sectional areas of the injured region were comparable in media (33 ± 5 versus 27 ± 2) and neointima (135 ± 16 versus 97 ± 17) of CD9+/+ and CD9−/− arteries. Immunocytochemical analysis revealed expression of CD9 in the endothelium, by SMC in the media and by some fibroblasts in the adventitia of non-injured femoral arteries. Three weeks after injury, there appeared to be a gradient of increased CD9 expression from the adventitia to the neointima, in which SMC are abundantly present. Immunogold labeling and electron microscopy with non-injured femoral arteries of CD9+/+ mice confirmed the presence of CD9 at the surface of adventitial fibroblasts and in SMC or pericytes, as well as in the endothelium.Thus, in this model CD9 is highly expressed by migrating SMC, but deficiency of CD9 does not affect SMC migration or neointima formation after perivascular injury.
Keywords: CD9; tetraspanin; vascular injury; restenosis; gene-deficient mice